2020
DOI: 10.1111/ejh.13495
|View full text |Cite
|
Sign up to set email alerts
|

Marker chromosome is a strong poor prognosis factor after allogeneic HSCT for adverse‐risk AML patients

Abstract: Chromosome analysis is necessary for the diagnosis and risk classification of acute myeloid leukemia (AML). 1,2 Fragmented chromosomes whose origin cannot be identified from an existing autosomal or sex chromosome may be observed, termed marker chromosome (MC). MC is considered to originate from marked genomic instability. 3 It is a relatively common abnormality, and its incidence in AML was reported to be 6.6%-16.1%. 4,5 However, MC is currently not specifically considered in the risk classifications by the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, patients with altered airway structures and diminished immune defenses are susceptible to pulmonary infections and more vulnerable to cardiovascular complications. 24 Consequently, healthcare professionals are encouraged to offer active health education to patients, advise them to quit smoking two to three weeks before the surgery, and encourage appropriate physical activity to enhance cardiopulmonary function. Patients should be closely observed for signs of pulmonary distress and laboratory indicators, and prophylactic antimicrobial drugs should be administered to deter pulmonary infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients with altered airway structures and diminished immune defenses are susceptible to pulmonary infections and more vulnerable to cardiovascular complications. 24 Consequently, healthcare professionals are encouraged to offer active health education to patients, advise them to quit smoking two to three weeks before the surgery, and encourage appropriate physical activity to enhance cardiopulmonary function. Patients should be closely observed for signs of pulmonary distress and laboratory indicators, and prophylactic antimicrobial drugs should be administered to deter pulmonary infections.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with altered airway structures and diminished immune defenses are susceptible to pulmonary infections and more vulnerable to cardiovascular complications. 24 Consequently, healthcare professionals are encouraged to offer active health education to In recent times, certain researchers have expressed optimism that alternative methods to troponin testing could potentially curtail healthcare expenditures. However, this approach has led to a proportionate escalation in misdiagnoses and heightened mortality risk among patients.…”
Section: Discussionmentioning
confidence: 99%
“…In AML, Bochtler et al (2017) reported that marker chromosomes could arise from CCRs and predict adverse prognosis [ 154 ]. Marker chromosomes were also suggested to be a risk classification factor for AML with adverse cytogenetics [ 163 ].…”
Section: Mechanisms and Consequences Of Cinmentioning
confidence: 99%